Combining Bootstrapping Procedure and Citizen Science Data to Elucidate Waterbirds’ Dependence on Coastal Wetland - Duan, Houlang; Yu, Xiubo; Xia, Shaoxia; Liu, Yu (Frontiers in Marine Science, 2022)
Coastal wetlands of the Yellow Sea and Bohai Sea, China, along the East Asian–Australasian Flyway (EAAF) migratory route provide important stopover sites for waterbirds. Natural wetland loss caused by external stress has posed serious threats to the population of waterbirds. Elucidating the extent to which species depend on natural wetland and providing conservation and management recommendations for species are important steps toward relieving such population declines. We created a natural landscape (NL) index along the coastal wetlands of the Yellow and Bohai Seas, China, using the inverse distance-weighted nearest-neighbor approach. Then, we used a bootstrapping procedure to combine the NL index with 11,485 occurrence records for 80 waterbird species attributed to four functional groups (shorebirds, ducks, herons, and gulls) to quantify species’ dependence on coastal natural wetlands. Twenty-seven out of the 80 species selected (16 shorebird, 3 duck, 4 heron, and 4 gull species) significantly depended on natural wetlands. The shorebirds [standardized effect size (SES) = 4.37] and herons (SES = 2.56) were more dependent on natural wetlands than the ducks (SES = −0.02) and gulls (SES = −3.22). The threatened species (those classified as critically endangered, endangered, vulnerable, or near threatened) showed significantly higher dependence on natural wetlands than the non-threatened species (t = 2.613, df = 78, p < 0.05). Of the 27 species showing significant dependence on natural wetlands, only nine species were listed as national protected species. Threatened species that highly depend on natural wetlands need more attention as these species could face greater risk due to natural wetland loss.